Pengaruh Pendampingan Orang Tua Terhadap Motivasi Dan Prestasi Belajar Siswa Pada Mata Pelajaran Matematika Kelas Atas SDN 2 Kenteng Nogosari Tahun Ajaran 2015-2016 - SUPARJO, Fitriana Diah (2016)
The purpose of research is to know is there any influence parental guidance on motivation and student achievement in mathematics upscale SDN 2 Kenteng Nogosari 2015-2016 school year. This type of research is quantitative research. Place of research at SDN 2 Kenteng Nogosari, population in this study were all students to sample classes IV and V, which totaled 45 people, a way of sampling by stratified random sampling. The technique of collecting data using questionnaires and documentation. Data analysis using simple linear regression formula with SPSS. The results of the first hypothesis test is rx1y = 0.548 with 0.000 significance compared to α (0.05). Thus sig. rx1y <α (0.05) so that H0 is rejected, the conclusion mentoring parents have a positive and significant impact on student motivation. Achievement calculation of the second hypothesis test is rx1y = 0.244 with 0.107 significance compared to α (0.05). Thus sig.rx1y> α (0,05) so that H0 is accepted, the conclusion mentoring parents do not have a positive and significant impact on student achievement.